Multilingual policy in the Polish education system - Kucharczyk, Radosław (Glottodidactica, 2021)
The aim of this article is to reflect on the implementation modalities of educational policy promoting multilingualism in Poland, a country where linguistic and cultural variety remains relatively low. The article begins with a definition of the concept of “language policy”. Subsequently, the European Union’s directives promoting the policy of multilingualism in the educational context are presented. In this part, the focus is on the following aspects: modern foreign languages, regional and minority languages, certification of language skills and teaching of a curriculum subject integrated into foreign language instruction. The last part of the article concentrates on the implementation of the said directives in Poland. In the research, the author relies on statistical data from various sources to demonstrate that - even if Poland is considered a country where linguistic and cultural variety remains low - foreign (in a broad sense of the term), regional and minority languages are regaining their rightful place in the functioning of the state, including in the Polish education system.